Green efficient octanoic acid based supramolecular solvents for extracting active ingredients from Zanthoxylum bungeanum Maxim. peels. (10th January 2022) - Cai, Zi-Hui; Wang, Jian-Dong; Wang, Li-Tao; Zhang, Su; Yan, Xin-Yu; Wang, Yan-Qiu; Zhao, Peng-Quan; Fu, Li-Na; Zhao, Chun-Jian; Yang, Qing; Meng, Dong; Fu, Yu-Jie
Abstract: Green vortex-assisted octanoic acid-ethanol-water supramolecular solvents (OAEW-SUPRAS) were developed for the simultaneous extraction of six phenolics and hydroxy-α-sanshool (HAS) from Zanthoxylum bungeanum Maxim. peels (ZBMP). The formation of OAEW-SUPRAS was composed of reverse micelle droplets with different sizes, which were caused by desolvation and aggregation. OAEW-SUPRAS were characterized by microscopy and fourier transform infrared spectroscopy. OAEW-SUPRAS can quickly extract active ingredients with different polarity and obtain excellent extraction yields (9.62 mg/g for phenolics and 41.08 mg/g for HAS). The proposed method was reliable (determination coefficients >0.99), precise (intra-day precision <5.04% and inter-day precision <7.29%) and accurate. The accuracy of the method ranged from 96.1 to 107.5%. The established secondary kinetic models (R 2 > 0.99) were proved a good fit with the extraction process. Under the optimal conditions, the efficiencies of active ingredients extracted by OAEW-SUPRAS were substantially higher than conventional organic reagents and the OAEW-SUPRAS extracts also showed a high antioxidant capacity (IC50 = 1.49 mg/mL). Finally, the extraction solvent and target compounds were easily recovered and enriched. Graphical abstract: Image 1 Highlights: Supramolecular solvents were used to extract phytochemicals from Zanthoxylum bungeanum peels. The reverse micelles accumulate and form supramolecular solvents consisting of different droplets. The green supramolecular solvents provided higher extraction yield than organic reagents. The solvents and target compounds can be easily recovered and enriched by adding water.